SMART transfer method to directly compare the mechanical response of water-supported and free-standing ultrathin polymeric films - Luke A. Galuska; Eric S. Muckley; Zhiqiang Cao; Dakota F. Ehlenberg; Zhiyuan Qian; Song Zhang; Simon Rondeau-Gagné; Minh D. Phan; John F. Ankner; Ilia N. Ivanov; Xiaodan Gu (Nature Communications, 2021)
Intrinsic mechanical properties of sub-100 nm thin films are markedly difficult to obtain, yet an ever-growing necessity for emerging fields such as soft organic electronics. Here, the authors present a shear motion assisted transfer technique for fabricating free-standing sub-100 nm thin films and measuring their inherent structural–mechanical properties.